Dyskerin expression in human fetal, adult and neoplastic intrahepatic bile ducts: correlations with cholangiocarcinoma aggressiveness1. Issue 2 (13th November 2014) - Vasuri, Francesco; Rocchi, Laura; Degiovanni, Alessio; Giunchi, Francesca; Brandi, Giovanni; Treré, Davide; Montanaro, Lorenzo; D'Errico‐Grigioni, Antonia
<x xml:space="preserve">Abstract</x> Aims To investigate the immunohistochemical expression of dyskerin, a biomarker involved in ribosome production and telomere maintenance, in human fetal, adult and neoplastic bile ducts, and possible correlations with cholangiocarcinoma aggressiveness. Methods and results Sixty consecutive intrahepatic cholangiocarcinomas were collected and used for tissue microarray construction (total: 176 cores); clinical data and follow‐up were also collected. Five fetal and 10 normal adult livers were included as controls. Automated immunohistochemistry for dyskerin, p53, and Ki67, and nucleolar silver staining, were performed. In normal livers, dyskerin expression was negative in smaller bile ducts (mean 44.8 μm) and positive in bile ducts of larger diameter (mean 116.1 μm; P < 0.001). Expression was positive in 56.7% of cholangiocarcinomas, and correlated with p53 mutation (P = 0.008) and a higher proliferative (Ki67) index (P = 0.003), which were included as markers of tumour aggressiveness. Finally, dyskerin‐positive cholangiocarcinomas showed a negative trend in disease‐free survival (P = 0.078) on univariate analysis. Conclusions The non‐neoplastic biliary tree seems to progressively lose dyskerin expression from the major branches to the peripheral portal bile ducts. Similarly, intrahepatic cholangiocarcinomas showed two patterns of dyskerin expression, and the dyskerin‐positive phenotype seemed to characterize more aggressive cholangiocarcinomas.